Exploring the Impact of Supplier Development Practices on Manufacturing Responsiveness in Malaysia - Tukiman, Rahayu (International Journal of Integrated Engineering, 2020)
Responsiveness in manufacturing is now a key to a competitive edge in an advanced manufacturing environment. The mutual relationship with a supplier is important in formulating the responsive supply chain. Therefore, this study is carried out to discover the extent of supplier development (SD) practices in influencing the manufacturing responsiveness (MR) to the manufacturing firms particularly in Malaysia. Data was collected from 71 manufacturing firms that accredited ISO 14001 via survey questionnaires. The results reveal that the development of suppliers has a positive and meaningful impact on MR. However, not all SD practices correlate equally to the MR practices. This finding can be used as a guideline for the manufacturing industry, mainly in Malaysia to understand better and deeper valuable information on the impact of SD practices towards manufacturing responsiveness as well as strengthening the SD practices to further enhance a responsiveness level in manufacturing.